2000
DOI: 10.2214/ajr.175.4.1751169
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Vascular Flow

Abstract: Transrectal sonography revealed that prostate vascular flow increases dramatically after ejaculation and remains elevated for at least 24 hr. This observation should be considered when power Doppler sonography is used to assess for potential hyperemia in patients suspected of having prostate abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It remains to be seen how our results may compare with those obtained in an older population with clinically significant disease. Second, the three quantitative parameters were imaged at a single time point immediately after ejaculation, and the time course of the effected changes, which could persist for more than 24 hours (19), was not mapped. This could be addressed by conducting serial imaging during the 1–2 hours after ejaculation or by performing repeat imaging after a longer interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen how our results may compare with those obtained in an older population with clinically significant disease. Second, the three quantitative parameters were imaged at a single time point immediately after ejaculation, and the time course of the effected changes, which could persist for more than 24 hours (19), was not mapped. This could be addressed by conducting serial imaging during the 1–2 hours after ejaculation or by performing repeat imaging after a longer interval.…”
Section: Discussionmentioning
confidence: 99%
“…An ultrasonographic (US) study documented that ejaculation can affect imaging results, showing that ejaculation increases blood flow to the prostate for at least 24 hours, which affected the clinical assessment of prostatitis (19). Similarly, ejaculation could effect changes in T2 and apparent diffusion coefficient (ADC) values in the prostate or in the T2- or ADC-based contrast between normal and cancerous tissue.…”
mentioning
confidence: 99%
“…The severity of prostate texture nonhomogeneity was classified using an arbitrary Likert scale and scores of 0–3 (0 = homogeneous texture, 1 = mild, 2 = moderate and 3 = severe texture nonhomogeneity). Prostate vascularization, prostate hyperemia and arterial prostatic peak systolic velocity (APPSV) were defined based on previous studies23243637 and evaluated prior to ejaculation to avoid post-ejaculatory changes in vascular flow pattern as has been previously reported 38. Seminal vesicle ultrasound features and abnormalities were defined based on previous studies 2325333940.…”
Section: Methodsmentioning
confidence: 99%
“…Morgan et al [ 23 ] showed that a greater than 10% reduction in whole-gland ADC value in patients on active surveillance predicted progression to radical treatment; if such cut-offs are to be used, this needs to be considered in light of the 5% reduction in whole-gland ADC we demonstrated at day 1. Although we did not look at the question of dynamic contrast-enhanced MRI, it is possible that this may also be affected by post-ejaculatory status, with a previous ultrasound study showing that ejaculation affected the clinical assessment of prostatitis by increasing prostatic blood flow for at least 24 h [ 24 ].…”
Section: Discussionmentioning
confidence: 99%